Visible light and fulvic acid assisted generation of Mn(III) to oxidize bisphenol A: The effect of tetrabromobisphenol A. (1st February 2020) - Yao, Jiayi; Qu, Ruijuan; Wang, Xinghao; Sharma, Virender K.; Shad, Asam; Dar, Afzal Ahmed; Wang, Zunyao
Abstract: Bisphenol A (BPA) and tetrabromobisphenol A (TBBPA), endocrine disrupting compounds (EDCs), are of increasing concerns for many years. This paper presents the elimination of BPA under visible light (VL) (λ ≥ 420 nm) irradiated solutions containing fulvic acid (FA) and MnSO4 (Mn(II)), and examines the possible effects of TBBPA on the transformation of BPA. After 72 h of reaction time, the removal efficiency of BPA in the studied system was 69%. Results of different experiments to identify oxidative species suggested the dominate role of soluble manganese (III) (Mn(III)) in the conversion of BPA. The transformation of BPA by the VL/FA/Mn(II) system was through self-oligomerization in absence of co-existence of TBBPA. In the co-existence of BPA with TBBPA, the removal of BPA was largely inhibited due to the competition with available Mn(III) and the possible occurrence of cross-coupling reactions between the two EDCs. This phenomenon was further elucidated by product analyses and density functional theory (DFT) calculations. The energy difference (Δ E ) for generating a cross-coupling product was calculated as −23.4 kJ mol −1, much lower than the positive values of Δ E for self-coupling products of BPA or TBBPA, demonstrating that cross-coupling reactions between BPA and TBBPA likely occurred easier than the respective self-coupling reactions. The toxicity test showed that the overall estrogenic activity of BPA reaction solution was significantly decreased by the VL/FA/Mn(II) system. In general, our study provided new insights into the transformation of co-existing EDCs by in situ formed Mn(III) in aqueous solution. Graphical abstract: Image 1 Highlights: BPA was removed by soluble Mn(III), in-situ formed in VL/FA/Mn(II) system. The co-existence of TBBPA inhibited the transformation of BPA by Mn(III). Self-oligomerization was the leading reaction pathway of BPA. Proposed pathways of oxidation of BPA were consistent with theoretical calculations.